Surrendering to the Big Picture: Historical and Legal Perspectives on Accountability in the Democratic Republic of Congo Following the Defeat of the March 23 Movement. Issue 1 (17th February 2014) - McKnight, Janet
It remains to be seen whether the past few months will mark a genuine turning point in the conflict in eastern Democratic Republic of Congo (DRC), as the rebel faction March 23 Movement (M23) announced the end of its 20-month insurgency against the government on 5 November 2013. News of the rebel group's surrender following its political and military defeat signals an important moment of hope and renewed prospects of peace and stability in a region prone to protracted armed conflict. However, long-term stability in the country and in the region will require a multi-faceted process consisting of comprehensive accountability for human rights violations that have been committed by all parties to the conflict. In this article, I will first lay out the historical context of the fighting and the root causes of conflict present long before M23's entrance onto the scene as a splintered rebel faction so as to understand M23's place within the country's history of protracted violence. Next, I will explain the violations of international humanitarian and human rights law committed by all possible parties, including rebel and government groups, as well as individual criminal responsibility and corporate liability. Lastly, I will chart the pathways of criminal and social accountability at various levels of international and domestic justice systems to see how the DRC may continue to build long-term local stability in the eastern parts of the country by addressing the question of accountability for international crimes. This brief analysis aims to provide a broader understanding of a complex conflict beyond the defeat and disarmament of M23, albeit a key group in a region of contentious cross-border conflict.